(untitled) (LEGAL DIALOGICA, 2025)
This study aims to identify and explain the roles and functions of the Narcotics Investigation Unit in combating narcotics crimes in Jeneponto Regency, as well as to identify and explain the factors that influence the roles and functions of the Narcotics Investigation Unit in addressing narcotics offenses in Jeneponto Regency. This research employs an empirical approach, which refers to written regulations or other secondary legal materials, to observe their application through field research conducted using sociological methods and interviews. This allows for a clearer understanding of the subject under study. The results of this study indicate that the Narcotics Investigation Unit in Jeneponto Regency plays a crucial role in efforts to combat narcotics crimes. Its main functions include preventive and repressive actions, as well as investigation and inquiry into narcotics-related crimes. Narcotics offenses in Jeneponto Regency present various internal and external challenges. Internally, limitations in human resources with specialized expertise in narcotics handling, along with inadequate facilities and infrastructure, are the main obstacles in task execution. Externally, a lack of coordination between related institutions further hinders effectiveness. Abstrak: Penelitian ini Untuk mengetahui dan menjelaskan Bagaimana peran dan fungsi Satuan Reserse Narkoba dalam penanggulangan tindak pidana narkotika di Kabupaten Jeneponto serta Untuk mengetahui dan menjelaskan faktor apa saja yang mempengaruhi peran dan fungsi Satuan Reserse Narkoba dalam penanggulangan tindak pidana narkotika di Kabupaten Jeneponto. . Penelitian ini menggunakan jenis penelitian empiris, yaitu suatu pendekatan yang mengacu pada peraturan-peraturan tertulis atau bahan-bahan hukum lainnya yang bersifat sekunder, untuk melihat bagaimana penerapan/pelaksanaannya melalui suatu penelitian lapangan yang dilakukan dengan sosiologis dan wawancara, sehingga dapat diperoleh kejelasan tentang hal yang di teliti. Hasil penelitian ini bahwa Satuan Reserse Narkoba di Kabupaten Jeneponto memiliki peran yang sangat penting dalam upaya penanggulangan tindak pidana narkotika. Fungsi utamanya mencakup tindakan preventif, represif, serta penyelidikan dan penyidikan terhadap pelaku kejahatan narkotika. Tindak pidana narkotika di Kabupaten Jeneponto menunjukkan bahwa terdapat berbagai kendala yang bersifat internal maupun eksternal. Secara internal, keterbatasan sumber daya manusia yang memiliki keahlian khusus di bidang penanganan narkotika serta minimnya sarana dan prasarana yang memadai menjadi hambatan utama dalam pelaksanaan tugas. Sementara itu, secara eksternal, kurangnya koordinasi antara lembaga terkait.